Legal Nature of Contract for Provision of State Medical Services - KOLISNYKOVA, Hanna V.; LEKHKAR, Oksana V.; SAMSONOVA, Yana О. (Journal of Advanced Research in Law and Economics; Vol 10 No 7 (2019): JARLE Volume X Issue 7(45) Winter 2019, 2019)
The relevance of the research is the contract provisions for private medical services have been thoroughly developed in scientific-legal doctrine; many studies analyze their content, classification, application. The legal essence of contracts on State (public) medical services in the current legislation of Ukraine, is not sufficiently researched that makes the issue in this area relevant. The purpose of the study is aimed at defining the concept and legal nature of contract provision for public medical services; generalization and critical understanding of the legislator's approaches to determining the role and significance of public medical service contracts in the system of contracts in Ukraine. The research main methods are dialectical, formal-logical, systemic. In particular, the systemic method was used to determine the place of the contract in the contract system as a whole. Special mention should be made of the specific scientific methods (comparative-legal, formal-legal) which were utilized to find out the legal nature of the public medical service contracts. The relevance of the research: the provisions on contract for provision private medical services are thoroughly developed in scientific-legal doctrine; many studies analyze their content, classification, application. The legal essence of the contract on public medical services in the current legislation of Ukraine, has not been sufficiently researched that that requires further examination. The research results are based on the analysis of regulatory material. It is concluded that there is no single agreed approach regarding the procedure for concluding these contracts, determining their legal nature and contract conditions in Ukraine. The authors emphasize on the recognition of the health of an individual as the highest social value of the European community, necessity of effective mechanisms for regulating health care relationships in order to achieve the highest level of health standards for all human beings, and improvement of the quality of life in general and health care in particular. The authors note that further expansion of public-private partnerships in the medical field is useful and necessary for all countries in the world. The medical services provision by public health institutions may be provided on the basis of private civil contracts. Practical significance is evident from the analysis of the normative material. The authors outline the main problematic issues regarding the legislative regulation of state medical contract and make specific proposals for improvement of the existing legislation in the medical service field. The worldwide pandemic COVID-19 has shown that effective mechanisms to regulate health care delivery relations in order to achieve the highest standard of health for all humanity and improve the quality of life in general, and health care in particular is a pressing issue for both developed countries and those seeking it. The conclusions and suggestions made can be used in the research sphere for further elaboration of problems of contract law, in the sphere of practical activity, in particular to develop contract forms.